Family adhesion to the kangaroo method: the importance of the nursing team (Research, Society and Development, 2020)
Objective: to identify in the national scientific literature, scientific productions about the importance of the nursing team in adhering to the Kangaroo Method by the family. Methodology: an integrative review carried out in the Latin American and Caribbean Health Literature and Nursing Database, using the descriptors “Newborn” and “Nursing” and “Kangaroo Method”. The search was carried out in July and August 2019. Results: The study consisted of 15 articles which showed that the nursing team is essential to ensure the implementation of the Kangaroo Method in neonatal units and to enable the method's adherence by the family of the newborn hospitalized. Final Considerations: The realization of this study made it possible to verify that nursing professionals are essential in carrying out the Kangaroo Method, since they are full-time with the baby and the family, have a more humanized and welcoming look, with a focus on the care for human beings.